(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to investigate the surface water quality of the Tista River at Kaunia point in wet (September to November) and dry season (December to February) during the period from September 2013 to February 2014. The water samples were collected from five different sampling stations of Tista River mentioned as Station 1 (St-1), 2 (St-2), 3 (St-3), 4 (St-4) and 5 (St-5). The analysis of the study showed that the average transparency was 13.28 and 32.31 cm in wet and dry season, respectively, while the temperature was observed 25.86 and 18.18?C in wet and dry season, respectively. The observed electrical conductivity (EC) was 84 and 145.67 ?s cm-1, pH was 7.72 and 8.03, dissolve oxygen (DO) was 5.35 and 5.37 mg l-1, biochemical oxygen demand (BOD) 1.64 and 1.89 mg l-1 in wet and dry season, respectively. In wet season, the total dissolved solid (TDS) was measured 53.2 mg l-1, while 73.86 mg l-1 in dry season. The alkalinity was found 40.94 and 43.4 mg l-1 in wet and dry season, whereas, the hardness was found 98.47 and 102.46 mg l-1 in the following seasons. The study showed that most of the water quality parameters of the Tista River were suitable for aquatic organisms as well as fishes. However, the agricultural runoff and waste materials generated from anthropogenic sources could be the main causes of degradation of water quality and aquatic organisms. J. Environ. Sci. & Natural Resources, 8(1): 29-33 2015